Comparison of Mean Healing Time Between Topical Nitroglycerin and Lateral Internal Sphincterotomy for Chronic Anal Fissure - Ivon Ijaz Bhatti, Rajia Nayaar, Aamer Wadud, Arsalan Siraj, Abbas Hassnain Kazmi, Abdul Wali Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Chronic anal fissure is a painful anorectal condition resulting from a longitudinal tear in the anoderm, often associated with internal anal sphincter hypertonia. Management options include pharmacological agents such as topical nitroglycerin and surgical procedures such as lateral internal sphincterotomy, each with distinct benefits and risks. Objectives: To compare the mean healing time and complication rates between topical nitroglycerin and lateral internal sphincterotomy in patients with chronic anal fissure. Study Design & Setting: A prospective comparative study was conducted at the Department of General Surgery, HITEC Institute of Medical Sciences and HIT Hospital Taxilla. Methodology: A total of 130 patients with chronic anal fissure were enrolled and randomly allocated into two equal groups: topical nitroglycerin (n=65) and lateral internal sphincterotomy (n=65). Demographic data, baseline characteristics, healing time, and complications were recorded. Healing was defined as complete epithelialization without symptoms, and patients were followed until recovery. Statistical analysis was performed using independent t-test and chi-square test, with p<0.05 considered significant. Results: The mean healing time was significantly shorter in the lateral internal sphincterotomy group (14.12 ± 2.93 days) compared to the topical nitroglycerin group (27.12 ± 4.50 days; p<0.001). Complications were observed in 5 (7.7%) patients in the topical nitroglycerin group and 3 (4.6%) patients in the surgical group, with a statistically significant difference in complication distribution (p=0.045). Conclusion: Lateral internal sphincterotomy resulted in significantly faster healing compared to topical nitroglycerin, with a low and acceptable complication rate. It remains the more effective option for chronic anal fissure when rapid recovery is desired. Keywords: anal fissure, healing time, lateral internal sphincterotomy, nitroglycerin, sphincterotomy, surgical treatment, topical therapy